PERAN MEDIA SOSIAL DALAM PROMOSI PARIWISATA PANTAI TELUK GURITA - Sonia M. Rosa De Sena; Julian Andriani Putri (LPSDI Bina Patria, 2025)
Teluk Gurita Beach, located in Belu Regency, East Nusa Tenggara, is one of Indonesia’s border tourism destinations with Timor Leste that holds significant natural and cultural potential, yet remains relatively unknown. The lack of conventional promotional efforts has highlighted the need for a digital strategy utilizing social media to increase the visibility of this destination. This study aims to analyze the role of social media in promoting local tourism and how tourism actors and local communities utilize platforms such as Instagram, Facebook, and TikTok to disseminate information and attract visitors. A descriptive qualitative approach was employed, using in-depth interviews, participatory observation, and document analysis as data collection techniques. The results indicate that social media serves as an effective tool for building destination image and significantly increasing tourist visits. Moreover, community involvement, especially among youth, enhances visual content promotion and digital participation. However, challenges such as limited internet access, lack of digital marketing training, and inadequate documentation equipment remain obstacles. This research highlights the importance of collaboration among government, communities, and tourism stakeholders to strengthen social media-based destination promotion in border regions.